Analysis of safety of bioactive concentrate of small sea fish therapy in comorbid patients with osteoarthritis - O. V. Zimnitskaya; M. M. Petrova; P. A. Shesternya (Современная ревматология, 2021)
The article discusses the safety issues of a bioactive concentrate of small sea fish (BCSSF, Alflutop®) in the treatment of osteoarthritis (OA). The data of original studies, which were published during 2001–2021 years, from eLIBRARY, PubMed and Web of Science databases were analyzed. The selection of studies was carried out according to the following criteria: diagnosis of OA or nonspecific back pain; follow-up duration ≥1 month; intramuscular or intra-articular route of BCSSF administration; ≥30 study participants; availability of information about adverse events.The accumulated data confirm the safety of BCSSF, including in patients with high comorbidity. The drug has no significant effect on serum levels of glycemia, electrolytes and protein metabolism. These results indicate the possibility of widespread use of this drug in the treatment of OA of peripheral joints and spine in patients with comorbid diseases.